Pseudo-Rules For Pseudo-Directors: The Problem Of Rules And Standards In Yap Sing Hock V Public Prosecutor - Hirsch, Steven A (Journal of Malaysian and Comparative Law, 2019)
Pseudo-Rules For Pseudo-Directors: The Problem Of Rules And Standards In Yap Sing Hock V Public Prosecutor – Steven A Hirsch